An interview with Richard Burrows about the Media Arts Standards: A pathway to expression and knowing the world. Issue 3 (2nd July 2016) - Albert, Daniel J.
ABSTRACT: Media arts has been familiar to many through television, film, and digital graphics, and often appears as an extension of the four traditional arts disciplines: music, arts, theatre, and dance. As media arts continues to acquire its own unique identity, particularly through technological means, it has been included as a stand-alone discipline in the National Core Arts Standards with its own set of K–12 standards. However, K–12 educators and administrators may be unsure of what constitutes media arts, how to teach it, and how to address the Media Arts Standards within a K–12 arts curriculum. Richard Burrows, Media Arts co-chair to the National Coalition for Core Arts Standards and member of the Media Arts Standards writing team, recently provided his thoughts on how media arts can be defined for curricular purposes. The interview also included a discussion of the construction process of the Media Arts Standards, certification and licensure for teaching media arts, a possible media arts teacher education curriculum, and the purpose of Model Cornerstone Assessments.